HUKUM SHOLAT JUM’AT SECURITY SHIFT PERSPEKTIF ULAMA FIKIH KONTEMPORER - Sa'adah, Umi Zahrotus; Gafur, Abd. (MUSLIM HERITAGE, 2024)
AbstractThe emergence of various problems which Islamic law in the contemporary era often raises questions in the community. So it is important that there is a contribution from contemporary fikih scholars to answer these problems. This study aims to explore the law of Friday prayers security shift perspective of contemporary fiqh scholars. The writing of this article uses the library research method, using various pieces of literature related to the discussion points. Thus, this research produces findings that contemporary scholars agree that security shifts are included in the category of udzur syar’i, so they are not required to perform Friday prayers but are required to replace them with four rokaat dhuhr prayers. AbstrakMunculnya berbagai problematika hukum Islam pada era kontemporer, sering menimbulkan pertanyaan pada masyarakat. Sehingga penting adanya andil dari para ulama fikih kontemporer untuk menjawab problematika tersebut. Studi ini bertujuan untuk menggali hukum sholat jum’at security shift perspektif ulama fikih kontemporer. Penulisan artikel ini menggunakan metode library research dengan menggunakan berbagai literature yang bersangkutan dengan poin pembahasan. Dengan demikian penelitian ini menghasilkan temuan bahwa ulama kontemporer sepakat menyatakan bahwa security shift termasuk dalam kategori udzur syar’i, sehingga tidak diwajibkan melaksanakan sholat jum’at namun diwajibkan untuk menggantinya dengan sholat dzuhur 4 rokaat.